2018
DOI: 10.1371/journal.pone.0202725
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of immune checkpoint inhibitors: A retrospective study in Taiwan

Abstract: BackgroundSince 2012, several immune checkpoint inhibitors have been approved by the Taiwan FDA for various types of cancer treatment. However, none of them are covered by Taiwan National Health Insurance due to the fact that they are expensive, and there is a lack of clinical evidence as to their effectiveness.ObjectivesThis study was aimed toward an exploration of clinical experiences with use of immune checkpoint inhibitors, including indications, prescription types, drug effectiveness, adverse drug event t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Off-label use of checkpoint inhibitor drugs can be notable, with estimates of between 18% and 30%, depending on the drug and study. 22,23 Popular articles have described the use of “desperation oncology,” in which immunotherapy is used to treat a variety of malignant neoplasms in patients nearing death. 24,25 Estimating off-label use is difficult, as there is no reliable registry showing how many patients are exposed to therapy and what percentage respond.…”
Section: Discussionmentioning
confidence: 99%
“…Off-label use of checkpoint inhibitor drugs can be notable, with estimates of between 18% and 30%, depending on the drug and study. 22,23 Popular articles have described the use of “desperation oncology,” in which immunotherapy is used to treat a variety of malignant neoplasms in patients nearing death. 24,25 Estimating off-label use is difficult, as there is no reliable registry showing how many patients are exposed to therapy and what percentage respond.…”
Section: Discussionmentioning
confidence: 99%
“…Common side effects include fatigue, pruritus, diarrhea, pyrexia, cough, dyspnea, musculoskeletal pain, constipation and nausea. Immune-mediated adverse events such as pneumonitis, colitis, hepatitis and thyroid disorder have been reported [10,11]. With the broad use of anti-PD-1 drugs in clinical practice, rarer side effects are emerging.…”
Section: Introductionmentioning
confidence: 99%
“…[475658596061] For example, in a retrospective study of 50 patients with nonsmall cell lung cancer, who were treated with an immune checkpoint inhibitor, the most frequent irAEs were fatigue (42%), rash (22%), nausea (20%), and fever (20%). [62] Similarly, a retrospective analysis to assess the safety profile of nivolumab in 576 patients with advanced melanoma found that 71% of patients experienced irAEs, with the most common irAEs being fatigue (25%), pruritus (17%), diarrhea (13%), and rash (13%). [63]…”
Section: Categories Of Immunotherapymentioning
confidence: 99%